PERAN KEPUASAN PELANGGAN SEBAGAI MEDIASI PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN EL RADNA SKINCARE CLINIC - Erma Widyastuti; Al Ghazali , Buya (Jurnal Manajemen & Bisnis Jayakarta, 2024)
Self-care has become a necessity and lifestyle for everyone, especially for women. The rapid development of beauty clinics requires companies in the beauty industry to understand the behavior of their consumers. The aim of this research is to explain the influence of service quality, customer satisfaction, and customer loyalty, as well as to elucidate the mediating role of customer satisfaction in the influence of service quality on customer loyalty. This study was conducted at El Radna Skincare Clinic. The sample in this study consisted of individuals who have used products from El Radna Skincare Clinic and have undergone some treatments at the clinic. The sampling method used was nonprobability examining. Data collection in this research employed a survey method with data collection techniques using questionnaires. Data were analyzed using path analysis techniques. The results of the study indicate that service quality has a positive and significant influence on customer satisfaction, service quality has a positive and significant influence on customer loyalty, customer satisfaction has a positive and significant influence on customer loyalty, and customer satisfaction significantly mediates the relationship between service quality and customer loyalty. The implications of this research include theoretical and practical implications. Keywords: · Service Quality, Customer Satisfaction, Customer Loyalty